Reducing missed opportunities for vaccination in selected provinces of Mozambique: A study protocol - Magadzire, Bvudzai Priscilla (Gates Open Res, 2017)
Background: A missed opportunity for vaccination (MOV) refers to any contact with health services by an individual who is eligible for vaccination, which does not result in the person receiving the vaccine doses for which he or she is eligible. A consortium of partners, including VillageReach, the Ministry of Health in Mozambique and the World Health Organization, will implement a strategy to reduce MOV in Mozambique. The strategy involves demonstrating the magnitude of missed opportunities and their causes, and exploring tailored health system interventions to reduce them, with the aim of increasing vaccination coverage and timeliness of vaccinations. Methods: A mixed-methods approach will incorporate both quantitative and qualitative tools. The assessment will target caregivers of children between the ages of 0–23 months who attend a health facility in the selected districts on the day of the assessment. Caregivers who are at least 18 years old will be eligible for inclusion. Another component of the assessment will target all health workers in the selected health facilities on the day of the assessment. A sample of 30 health facilities in different regions of the country will be assessed, with a target sample size of 600 caregiver exit interviews, 300 health worker interviews and focus group discussions with both caregivers and health workers. Data collection will commence late 2017, and the data will be electronically captured, managed and analyzed. Thematic analysis of data from the qualitative aspects of the assessment will be conducted, presenting the scope of interviews, representative verbatim quotes and key conclusions.  Conclusions: A concerted effort to reduce or eliminate MOV could increase vaccine coverage by up to 30% and may contribute to wider improvements in efficiencies of service delivery beyond the immunization program. In addition, the findings could contribute to a better understanding of MOV in similar settings.